2014
DOI: 10.1002/pc.23204
|View full text |Cite
|
Sign up to set email alerts
|

Injection‐molded parts of polypropylene/multi‐wall carbon nanotubes composites with an electrically conductive tridimensional network

Abstract: Polypropylene‐based composites filled with multi‐wall carbon nanotubes (MWCNTs), ranging from 1 to 6 wt%, were obtained by injection molding from a previous masterbatch compounded by twin‐screw extrusion (TSE). Resultant electrical percolation phenomenon was related to the ultrathin structure of the carbon‐based fillers and the high dispersion achieved in the thermoplastic matrix. In particular, conductivity experiments showed a threshold value of 3 wt% (1.3 vol%) of MWCNTs for percolation to occur. Electrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Once the biopolymer was melted by the reciprocating screw against the unmoving barrel wall, a metered dosage of polymer melt was transferred towards the nozzle of the injection unit and then injected into the mold, where the heat from the melt dissipates rapidly. In general, very high shear rates arise in injection molding operations, usually up to 10 4 s −1 [38]. A cavity filling time of 1 s was set during mold cavity filling to optimize the process, whereas a packing time of 10 s during back pressure was used to improve the final quality and properties of the green composite pieces.…”
Section: Visual Aspect Of Pla/fsf Composite Piecesmentioning
confidence: 99%
“…Once the biopolymer was melted by the reciprocating screw against the unmoving barrel wall, a metered dosage of polymer melt was transferred towards the nozzle of the injection unit and then injected into the mold, where the heat from the melt dissipates rapidly. In general, very high shear rates arise in injection molding operations, usually up to 10 4 s −1 [38]. A cavity filling time of 1 s was set during mold cavity filling to optimize the process, whereas a packing time of 10 s during back pressure was used to improve the final quality and properties of the green composite pieces.…”
Section: Visual Aspect Of Pla/fsf Composite Piecesmentioning
confidence: 99%
“…This is attributed to the higher aspect ratio and intrinsically higher electrical conductivity of CNT. In a recent study, Torres‐Giner et al . reported that p c occurs at 3 wt % for PP/CNT composites obtained by conventional injection molding.…”
Section: Introductionmentioning
confidence: 99%
“…[51] More importantly, due to the lower mixing energies and shear peaks employed during molding methodologies, filler attrition or breakage can be minimized. [52] In this work, pita fibers were originally selected to produce a sustainable LFRT. This hard-type fiber is extracted from the leaves of the agave plant (Agave americana), which is a monocotyledon plant from the sisal family of Agave sisalana.…”
Section: Introductionmentioning
confidence: 99%